Prospective Observational Study of Postoperative Outcomes Following Hepaticojejunostomy versus Hepaticoduodenostomy in Benign Biliary Pathology - Rumman Khan; Aqib Ali Khan (PKLI Journal of Health Sciences, 2026)
Background: Biliary–enteric anastomosis is an essential surgical procedure in benign biliary disease. Hepaticojejunostomy (HJ) and hepaticoduodenostomy (HD) are commonly employed, yet prospective comparative data remain limited. Objective: To compare short-term postoperative outcomes of HJ and HD in benign biliary pathology. Methods: This prospective observational study was conducted at a tertiary surgical hospital between January 2022 and June 2023. Eighty patients underwent biliary–enteric reconstruction: 55 received HJ and 25 underwent HD. Demographics, indications, complications, and recovery outcomes were recorded. Categorical variables were analyzed using Chi-square test, and continuous variables using independent samples t-test. Results: 80 patients were enrolled in our study, with 55 underwent hepaticojejunostomy (HJ) and 25 underwent hepaticoduodenostomy (HD). Common bile duct injury was the most common reason for surgery, followed by benign biliary stricture and choledochal cyst. Anastomotic leak occurred in 3 patients in the HJ group (5.5%) compared with 1 patient in the HD group (4.0%), with no significant difference (p = 0.85). Anastomotic stricture developed in 3 patients who underwent HJ (5.5%) compared with 1 case who underwent HD (4.0%), also not significant (p = 0.85). In the HJ group, two patients experienced early persistent jaundice, for which the interventional radiology team was involved; both underwent percutaneous transhepatic cholangiography (PTC) with balloon dilation, performed successfully and obstruction was relieved. Two patients in the HJ group (3.6%) died postoperatively, while no mortality was observed in the HD group (0%) with no statistical significance (p = 0.31). When major complications were assessed, worse outcomes occurred in 27.9% of HJ patients versus 8.0% of HD patients (p = 0.027). The average duration of hospital stay was longer in the HJ group (6.5 ± 1.5 days) compared with HD (4.0 ± 1.2 days, p < 0.001). Early oral intake by postoperative day 2 was attained in 74.4% of HJ patients and 93.9% of HD patients, a significant difference (p = 0.032). Conclusion: Both HJ and HD are safe and effective for benign biliary reconstruction. HD was associated with a significantly shorter hospital stay and a trend toward fewer complications. Larger multicenter studies with long-term follow-up are warranted.